PERFORMING AN ARITHMETIC OPERATION IN THE PYTHON PROGRAMMING LANGUAGE - Jurayev Sherali Umarjonovich (American Journals, 2023)
The creation of the Python programming language began in the early 1990s. At that time, Guido van Rossum, an employee of the Dutch CWI Institute, who was not well known, participated in the project of creating the ABC language. ABC was a language designed to teach students basic programming concepts instead of Basic. One day, Guido got tired of this work and spent 2 weeks writing an interpreter for another simple language on his Macintosh, during which he definitely absorbed some ideas of the ABC language.
Keywords: Python programming language, Internet, Macintosh, computer, information technology